Population Characterization of Planktonic Shrimp, Acetes japonicus (Decapoda: Sergestidae) using RAPD Technique - Deraman, Aziz; Siraj, Siti Shapor; Arshad, Aziz; Nurul Amin, Sanker Mohammad; Harmin, Sharr Azni (2010)
Genomic DNA of sergestid shrimp, Acetes japonicus was successfully extracted by using the Promega Wizard Genomic DNA Purification Kit. Population genetic characterization of A. japonicus along the western coast of Peninsular Malaysia (state of Perak, Malacca and Kedah) was examined using the Random Amplified Polymorphic DNA (RAPD) marker. Twenty oligonucleotides from operon A kit were used to screen the populations, of which 6 were able to be amplified (OPA03, OPA04, OPA07, OPA09, OPA10, OPA16). The percentages of polymorphic bands of the three populations investigated varied from 57.77 to 87.77%. Genetic distances between populations and cluster analysis from UPGMA grouped the populations into two major clusters. The Perak and Malacca populations were in one cluster, while the Kedah population was clustered by itself, indicating a different population. The genetic distance was highest as 0.0999 for the Kedah and the Malacca populations while lowest value was 0.0413 for the Perak and the Malacca populations, which probably have a closed ancestral relationship. The results of this study suggested that RAPD analysis, if carried out carefully and accurately would give a good indication of the separation between individuals of different populations and is suitable for identification of closely related genotypes.